Perlindungan Hukum terhadap Investor Perumahan Terkait Alih Fungsi Lahan Sawah yang Dilindungi di Kabupaten Serang - Babay, Babay; Purwaningsih, Endang; Yusuf, Chandra (AKADEMIK: Jurnal Mahasiswa Humanis, 2025)
The logical consequence for a growing city is an increase in population and shrinkage of rice fields and forests which are being converted into industry and residential areas. The Integrated Team for Controlling the Conversion of Rice Land in Serang Regency noted that there had been a reduction in rice fields covering an area of ​​15 thousand hectares from 2019 to 2022 in the Serang Regency area. This research was carried out to answer research questions regarding the concept of legal protection for housing investors in the transition of the function of rice fields in Serang Regency and how the provisions for the conversion of protected rice fields in Serang Regency are implemented. This research is normative juridical research using a statutory approach, a conceptual approach and an analytical approach. Data collection techniques were obtained by means of library research and data analysis using descriptive qualitative analysis. The results of this research are that currently there is no protection for investors regarding the legal conversion of protected rice fields. Rice fields which are then converted into residential land cannot be legally defined as ownership rights by the community because they stand on protected rice fields. Investors do not get transparent access regarding mapping of protected rice fields in Serang district, while the business licensing process has been issued and can be operated by housing investors.